2021
DOI: 10.2147/dmso.s284583
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio Predict Mortality in Patients with Diabetic Foot Ulcers Undergoing Amputations

Abstract: Purpose Elevated platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) are associated with poor outcomes in various diseases. The objectives of this study were to explore the utility of PLR and NLR in predicting all-cause mortality in patients with diabetic foot ulcers (DFU) undergoing amputations. Patients and Methods A retrospective observational study was performed that included a total of 348 DFU patients undergoing amputations. The primary end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 35 publications
0
34
1
Order By: Relevance
“…20 Another study reported that NLR and PLR were predictive factors of mortality following amputation. 19 However, mortality in that study was determined at 1, 3 and 5 years after amputation and whether NLR and PLR were determined at baseline or monitored during follow-up was not stated in the methods of the study. 19 This association should be clarified by further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Another study reported that NLR and PLR were predictive factors of mortality following amputation. 19 However, mortality in that study was determined at 1, 3 and 5 years after amputation and whether NLR and PLR were determined at baseline or monitored during follow-up was not stated in the methods of the study. 19 This association should be clarified by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, mortality in that study was determined at 1, 3 and 5 years after amputation and whether NLR and PLR were determined at baseline or monitored during follow-up was not stated in the methods of the study. 19 This association should be clarified by further studies. Neither PLR nor LMR were predictive factors for severe infections in either univariate or multivariate analysis in our experience.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that the severity of DFUs may be in part determined by the deficiency of the immune response in DFUs via deregulation of IL-6, macrophage migration inhibitory factor (MIF), and interferon-inducible protein (IP)-10 [ 118 ], and a compromised neutrophil response [ 119 , 120 , 121 ]. In recent years, it has been proposed that high platelet-to-lymphocyte (PLR) and neutrophil-to-lymphocyte ratios (NLR) may be a biomarker for DFU severity [ 122 , 123 ], where high PLR levels reflect the increased platelet activity, inflammation, and the risk for thrombosis and atherogenesis [ 122 , 124 , 125 ], while high NLR levels lead to the upregulation of cytokines and of proteolytic enzymes that can cause tissue damage [ 122 , 123 ].…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…While a full evaluation of DFU biomarkers is outside the scope of this review, briefly, some recent reports of wound exudate biomarkers for DFU wound healing include epithelial neutrophil-activating protein (ENA)-78 [ 254 ], c-x-c motif chemokine ligand 6 (CXCL6) [ 255 ], and MMP-9 [ 256 ]. A number of serum biomarkers have been identified, including albumin [ 257 ], PLR and NLR [ 122 , 258 ], angiopoietin-like 2 (ANGPTL2) [ 259 ], lipoprotein-associated phospholipase A2 and interleukin-18 (IL-18) [ 260 ], pentraxin 3 [ 261 ], T-cell differentiation markers [ 262 ], stem/progenitor cells [ 263 ], as well as neutrophil extracellular traps (NETs)-specific markers [ 264 ]. Recent genomic analyses of DFU have utilized circRNAs [ 265 , 266 , 267 ], lncRNAs [ 268 ], miRNAs [ 99 , 100 , 269 ], genetic polymorphisms [ 270 , 271 , 272 ], cytokine arrays [ 273 ], and network maps [ 274 ] for the identification of other potential biomarkers for DFU diagnosis and prognosis.…”
Section: Diagnostic Measuresmentioning
confidence: 99%
“…Increased NLR levels indicate endothelial damage and dysfunction as a result of increased neutrophil secretory activity, which can lead to an unfavorable prognosis in CVD [335]. According to the literature, in modern cardiology, studies have shown that NLR is an independent predictor of outcome in patients with stable coronary heart disease and a predictor of short -and long-term mortality in patients with acute coronary syndromes ((ST-segment elevation myocardial infarction) (STEMI)) and heart transplantation [333].…”
Section: змішаний стресmentioning
confidence: 99%